Optimal Assignment of Vehicles to Urban Transport Routes - Dusan Teichmann; Michal Dorda; Ivana Olivkova (Communications - Scientific letters of the University of Zilina, 2013)
The article deals with solving a concrete problem occurring in the tramway net conditions in Ostrava urban mass transport. Nowadays acertain tramway set is in the traffic, where different vehicle types in terms of the capacity are assigned. For every route, one vehicle type is used. Information about the offered capacity and the passenger flows per hour is known. But the existing assignment of vehicles to single routes causes agreater discrepancy in terms of offered places and passengers’ demand. The discrepancy can be measured by means of the ratio of these values on the most frequented route section. The discrepancy is characterized so that the ratios have very large deviation. In practice, it means that on the one hand there are routes with ahigh traveling comfort and on the other hand there are routes with alow traveling comfort. We can improve the situation by changing the vehicle types on single routes. At the same time we can reach the quality by improving offered services.